Training and Practice of Instructional Librarians: Cross-Population and Longitudinal Perspectives. Issue 2 (3rd April 2021) - Lund, Brady D.; Widdersheim, Michael; Fay, Brendan; Wang, Ting
ABSTRACT: This study examines the perspectives of instructional librarians, academic library administrators, and library school educators regarding the training and practice of instructional librarians. Semi-structured interviews were conducted with n = 37 participants from the three populations within the US and Canada. Inter-group responses were compared to explore similarities and differences between the groups. Responses were also compared to those from a similar study conducted in 1993. Findings indicate that training and practice related to instructional librarianship have changed over time. Compared to observations from 1993, librarians, administrators, and educators today observe that the demand for instruction has increased in the academic library workplace, fewer librarians enter the workplace with previous teaching experience, and library schools do a better job at providing instructional training than before. However, all respondent groups today placed increased responsibility on library schools to provided instructional training. Participants from all three populations today believe that library schools should continue to train students in instructional skills, although alternative modes of training were also recommended.